2014
DOI: 10.1016/j.ahj.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Addressing barriers to optimal oral anticoagulation use and persistence among patients with atrial fibrillation: Proceedings, Washington, DC, December 3-4, 2012

Abstract: Approximately half of patients with atrial fibrillation (AF) and with risk factors for stroke are not treated with oral anticoagulation (OAC), whether it be with vitamin K antagonists (VKAs) or novel OACs (NOACs); and of those treated, many discontinue treatment. Leaders from academia, government, industry, and professional societies convened in Washington, DC, on December 3–4, 2012, to identify barriers to optimal OAC use and adherence and to generate potential solutions. Participants identified a broad range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 65 publications
1
41
0
3
Order By: Relevance
“…Of total of VKA-treated patients, 1,820, ca 37 % patients discontinued the anticoagulant treatment within 6 months. This rate of discontinuation is similar to what has been reported in the literature, where discontinuation rate ranges from 20 to more than 50 % (15,24).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Of total of VKA-treated patients, 1,820, ca 37 % patients discontinued the anticoagulant treatment within 6 months. This rate of discontinuation is similar to what has been reported in the literature, where discontinuation rate ranges from 20 to more than 50 % (15,24).…”
Section: Resultssupporting
confidence: 77%
“…In particular, anticoagulant treatment is highly recommended for patients with CHADS2 or CHA2DS2-VASC scores ≥ 2. However, even if oral anticoagulation is effective in preventing strokes due to AF (12), there is extensive evidence suggesting that this therapy remains underused (4,10,(13)(14)(15). Despite, the data from the literature is clearly showing that the efficacy of antiplatelet agents in thromboembolic prevention is significantly lower than that of oral anticoagulant therapy (14).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…General considerations on oral anticoagulant therapy under-prescription in older patients with atrial fibrillation OAT is still widely underused in older subjects with AF: studies consistently demonstrate that less than half of octogenarians are currently treated with OAT [1,[4][5][6][7][8][9][10][11]24,[35][36][37][38]. Although temporary or permanent contraindications may partially account for this under-prescription [6,7], advanced age and short life-expectancy, fear of bleeding, perceived harm greater than benefit, poor health and geriatric syndromes appear to be the most common reasons why physicians withhold anticoagulants [4][5][6][7]14,[34][35][36][37]. It seems plausible that this persisting therapeutic reluctance relies on intimate skepticism that the clinical benefits demonstrated in randomized trials and observational studies may not be observed at the same extent in more vulnerable older patients.…”
Section: Geriatric Syndromes and Comprehensive Geriatric Assessmentmentioning
confidence: 99%
“…Furthermore, additional barriers to optimal use of anticoagulants include knowledge gaps about stroke risk extent and OAT benefit/harm balance, lack of recognition of expanded eligibility for OAT and DOACs in the elderly and in VKAs-unsuitable patients, and concerns about bleeding risk with novel DOACs [14].…”
Section: Introductionmentioning
confidence: 99%